2015
DOI: 10.1109/lsp.2014.2349356
|View full text |Cite
|
Sign up to set email alerts
|

Convex 1-D Total Variation Denoising with Non-convex Regularization

Abstract: Total variation (TV) denoising is an effective noise suppression method when the derivative of the underlying signal is known to be sparse. TV denoising is defined in terms of a convex optimization problem involving a quadratic data fidelity term and a convex regularization term. A non-convex regularizer can promote sparsity more strongly, but generally leads to a non-convex optimization problem with non-optimal local minima. This letter proposes the use of a non-convex regularizer constrained so that the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 20 publications
2
109
0
Order By: Relevance
“…Figure 2 shows that the proposed penalty yields the lowest average RMSE for all σ 0.4. However, at low noise levels, separable convexitypreserving penalties [48] perform better than the proposed non-separable convexity-preserving penalty.…”
Section: Examplementioning
confidence: 88%
See 1 more Smart Citation
“…Figure 2 shows that the proposed penalty yields the lowest average RMSE for all σ 0.4. However, at low noise levels, separable convexitypreserving penalties [48] perform better than the proposed non-separable convexity-preserving penalty.…”
Section: Examplementioning
confidence: 88%
“…This denoised signal consistently underestimates the amplitudes of jump discontinuities, especially those occurring near other jump discontinuities of opposite sign. Figure 1(c) shows the result using a separable non-convex penalty [48]. This method can use any nonconvex scalar penalty satisfying a prescribed set of properties.…”
Section: Examplementioning
confidence: 99%
“…Noise is easy to be separated into S for the reason that the rank of target matrix T is limited and the noise which may distribute in any part of the image also possesses sparse property. In order to distinguish the noise from S, we introduce a total variation model that is used in image denoising [41] and object detection [42] to impose a more accurate regularization on S:…”
Section: Appearance Modelmentioning
confidence: 99%
“…where, G(S) is a differentiable and convex function with Lipschitz continuous gradient and H(x) is a non-smooth but convex function [41].…”
Section: Appendix Amentioning
confidence: 99%
“…Besides the trend-setting works of Geman and McClure [4] and Chipot et al [6], the practical effectiveness of non-convex functionals have also been shown in other studies. In signal/image denoising, the researches of Aubert et al [1], Nikolova [17] and Selesnick et al [18] illustrate by concrete examples the better performance of some non-convex functionals as compared to convex ones. Vese [19] shows the ability of several non-convex potentials to reconstruct signals, being particularly accurate at restoring edges and linear regions.…”
Section: Functions Typementioning
confidence: 99%